Biomedical and business applications using artificial neural networks and machine learning - Segall, Richard, 1949-; Niu, Gao, 1987- (Engineering Science Reference, 2022)
"This book covers applications of artificial neural networks (ANN) and machine learning (ML) aspects of artificial intelligence to applications to the biomedical and business world including their interface to applications for screening for diseases to applications to large-scale credit card purchasing patterns"--